Kompetensi Pengadilan Tata Usaha Negara dalam Menyelesaikan Kasus Tanah tentang Hak Pengelolaan - Rafiqi, Rafiqi (Universitas Medan Area, 2017)
The Law of Execution in the Administrative Court is different from the law of execution in civil courts. The civil trial of execution law is supplemented by physical means, namely: Jita Sita, aid of State Instruments (Police) and so on, which can force fiction so that the losers obey the court's decision. In the Administrative Court it is not possible, the Administrative Court is only equipped with administrative facilities only, in accordance with its authority which only judges in terms of administrative legality (administrative court). Rights Management issued a letter of proof of rights in the form of a certificate of Right of Management by the Land Office. The management rights are the right to land. The purpose of legal certainty itself will be fulfilled if if a device or legal system that can run and support the achievement of a legal kepolisia, especially the role of institutions that are authorized